Mapping Innovative Human Resources in Economic and Business Development: A Bibliometric Analysis of Scopus Publications in East Kalimantan - Ahmad Hudaifah; Shochrul Rohmatul Ajija; Maulidy Albar; Wafa Abdania Zamzami (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2026)
Objective: To explore and identify the development stages of sustainable development and to examine the pace of human resource development in economic and business topics in East Kalimantan. Design/Methods/Approach: Bibliometric analysis using the Scopus database from 1979 to 2026, synthesising a total of 681 articles. Findings: There is an increasing number of reputable Scopus publications by East Kalimantan researchers focusing on critical topics such as biodiversity, forestry, and conservation. Active local researchers are collaborating with global networks, with Universitas Mulawarman emerging as the leading institution. The study identified 10 thematic clusters, revealing that the mining, oil, and gas industries drive innovation as a triple helix solution between research and stakeholders. Furthermore, innovative human resource development coexists with the increasing dynamics of economic and business development. Originality/Value: This study offers a novel contribution by applying a comprehensive bibliometric analysis and PRISMA guidelines specifically focused on human resource development within the economic and business landscape of East Kalimantan, a context that has not been extensively mapped in previous literature. Practical/Policy implication: The increasing dynamics of economic and business development create environmental issues—such as climate change, deforestation, ecological damage, and pollution—that require constructive solutions and sustainable development strategies.